The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/agronomy13112730
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Parameters and Identification of Leaf Blast-Resistant Rice RILs Using Cluster Analysis and MGIDI

Reza Jalalifar,
Atefeh Sabouri,
Sedigheh Mousanejad
et al.

Abstract: Rice blast disease, caused by the fungus Magnaporthe oryzae, poses a significant threat to rice cultivation. One effective way to deal with this disease is to identify and introduce resistant varieties using different breeding methods. This study utilized a population of 153 recombinant inbred lines (RILs) derived from the crossing of the Shahpasand (SH) and IR28 varieties, characterized by susceptibility and resistance to leaf blast, respectively. In combination with 12 control varieties, these genotypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, Olivoto and Nardino (2021) have indicated that MGIDI stands out as the most efficient index for selecting genotypes with desired characteristics, further reinforcing its applicability and effectiveness in crop improvement strategies. Jalalifar et al (2023) shed light on the promising prospects of selected rice genotypes through MGIDI in their study, emphasizing their careful selection as a valuable resource for breeding programs. These chosen genotypes serve as a foundation for creating recombinant populations through strategic crosses, fostering maximum genetic diversity for the development of new rice lines.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Olivoto and Nardino (2021) have indicated that MGIDI stands out as the most efficient index for selecting genotypes with desired characteristics, further reinforcing its applicability and effectiveness in crop improvement strategies. Jalalifar et al (2023) shed light on the promising prospects of selected rice genotypes through MGIDI in their study, emphasizing their careful selection as a valuable resource for breeding programs. These chosen genotypes serve as a foundation for creating recombinant populations through strategic crosses, fostering maximum genetic diversity for the development of new rice lines.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been successfully applied in various crop breeding programs for genotype selection, such as wheat [ 30 ], rice [ 31 ] and maize [ 32 ]. Jalalifar et al [ 33 ] have recently introduced an advanced tool that enables breeders to efficiently select the most desirable genotypes with resistance to leaf blast in rice considering the interaction between outcome across multiple years. Consequently, in present study, EMT is anticipated to contribute to increased rice yields and has the potential to alleviate insect pest pressures, thereby reducing the incidence of pest outbreaks and minimizing yield losses.…”
Section: Introductionmentioning
confidence: 99%